TRAIN CHILDREN'S ABILITY TO SOLVE PROBLEMS INTO MATHEMATIC THROUGH MONSTERM MATH ANIMATIONS: MELATIH KEMAMPUAN ANAK UNTUK MEMECAHKAN MASALAH KE DALAM MATIMATIKA MELALUI ANIMASI MONSTERS MATH - Sofyan, Fuaddilah Ali; Seftiana, Afil Fres; Oktariyani, Rizky; Pramuswari, Meilin Faiza; Asmara, Seftia Eka; Damaianti, Siska (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2022)
Abstract Some problems in learning mathematics such as students' lack of interest in learning to use media that only appear visually, many of them are not able to absorb lessons properly when taught using visual media, quite dangerous for children with mental retardation, because the media the learning media used are made of wood, as well as the limited number of animated/cartoon media procurement that is in accordance with the developmental stages of children with mental retardation. Based on this, the authors carry out activities to optimize the use of 3D animation learning media in mathematics for teachers in the form of training and mentoring activities. The results show that children's mathematical logic intelligence is developing. Developing children's mathematical logical intelligence can be developed through animation media in children's songs designed according to the theme of AUD learning. The use of animation media in songs can attract children's interest in using their imagination so that they are able to express ideas. Thematic-based animation media is a fun activity for young children.